Conceptions of Good Teaching by Good Teachers: Case Studies from an Australian University - Duarte, Fernanda (Journal of University Teaching and Learning Practice, 2013)
This paper contributes to the debate on what constitutes good teaching in early 21st Century higher education, through an examination of the experience of five outstanding lecturers from a business school in an Australian university. It is based on a qualitative study that explored their perceptions on what constitutes ‘good teaching’. Resonating with existing research on good teaching practice, the findings suggest that good teachers tend to embrace constructivist principles, and are committed to facilitating learning that is deep, engaged, experientially-based, empowering, reflective, and life-long. The real-life examples of good teaching practice provided by the participants are a valuable resource to higher education teachers, in particular those beginning their careers.